Acute amnestic syndrome in fornix lesions: a systematic review of reported cases with a focus on differential diagnosis - Mazzacane, F.; Ferrari, F.; Malvaso, A.; Mottese, Y.; Gastaldi, M.; Costa, A.; Pichiecchio, A.; Cavallini, A. (Frontiers in Neurology, 2024)
Introduction Acute amnestic syndrome is an uncommon clinical presentation of neurological disease. Differential diagnosis encompasses several syndromes including Wernicke-Korsakoff and transient global amnesia (TGA). Structural lesions of the fornix account for a minority of cases of acute amnestic syndromes. Etiology varies from iatrogenic injury to ischemic, inflammatory, or neoplastic lesions. A prompt diagnosis of the underlying pathology is essential but challenging. The aim of this review is to systematically review the existing literature regarding cases of acute amnestic syndrome associated with non-iatrogenic lesions of the fornix. Methods We performed a systematic literature search on PubMed, Scopus, and Web of Science up to September 2023 to identify case reports and case series of patients with amnestic syndrome due to fornix lesions. The systematic review was conducted according to PRISMA guidelines. The research was limited to articles written in English. Cases of fornix damage directly ascribable to a surgical procedure were excluded. Results A total of 52 publications reporting 55 cases were included in the review. Focusing on acute/subacute onset, vascular etiology was highly prevalent, being responsible for 78% of cases, 40/55 (74%) of which were due to acute ischemic stroke. The amnestic syndrome was characterized by anterograde amnesia in all patients, associated with retrograde amnesia in 27% of cases. Amnesia was an isolated presentation in most cases. Up to two thirds of patients had persistent memory deficits of any severity at follow-up. Discussion Acute amnestic syndrome can be rarely caused by fornix lesions. In most cases of acute/subacute presentation, the etiology is ischemic stroke, mainly caused by strokes involving the subcallosal artery territory. The differential diagnosis is challenging and a distinction from common mimics is often difficult on a clinical basis. A high index of suspicion should be maintained to avoid misdiagnosis and provide adequate acute treatment to patients with time-dependent disease, also employing advanced neuroimaging. More research is needed to better understand the outcome and identify prognostic factors in patients with amnestic syndrome due to fornix lesions.